2019
DOI: 10.5194/soil-5-205-2019
|View full text |Cite
|
Sign up to set email alerts
|

Spatially resolved soil solution chemistry in a central European atmospherically polluted high-elevation catchment

Abstract: Abstract. We collected soil solutions by suction lysimeters in a central European temperate forest with a history of acidification-related spruce die-back in order to interpret spatial patterns of soil nutrient partitioning, compare them with stream water chemistry and evaluate these parameters relative to concurrent loads of anions and cations in precipitation. Five lysimeter nests were installed in the 33 ha U dvou loucek (UDL) mountain catchment at different topographic positions (hilltops, slopes and valle… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 60 publications
0
8
0
Order By: Relevance
“…On the other hand, UHL and LYS exhibited high exchangeable acidity, and low base cations due to Ca-poor granite bedrock [86]. The UDL catchment was seriously affected by air-pollution, which caused forest decline in the past, and forest management interventions, particularly the application of dolomitic limestone between 1980 and 2007 [87], were most pronounced there. As a result, UDL catchment, naturally underlined by a Ca poor bedrock (orthogneiss) exhibited relatively low exchangeable acidity and high base saturation in the forest floor.…”
Section: Needle Traits and Soil Properties-site Effectsmentioning
confidence: 99%
“…On the other hand, UHL and LYS exhibited high exchangeable acidity, and low base cations due to Ca-poor granite bedrock [86]. The UDL catchment was seriously affected by air-pollution, which caused forest decline in the past, and forest management interventions, particularly the application of dolomitic limestone between 1980 and 2007 [87], were most pronounced there. As a result, UDL catchment, naturally underlined by a Ca poor bedrock (orthogneiss) exhibited relatively low exchangeable acidity and high base saturation in the forest floor.…”
Section: Needle Traits and Soil Properties-site Effectsmentioning
confidence: 99%
“…The distance between LYS and PLB is seven km. U Dvou Loucek (UDL; Eagle Mts., northeastern Bohemia [41,44,46,47]) is characterized by low Mg inputs via bedrock dissolution, and high Mg inputs via atmospheric deposition. The UDL bedrock is formed by orthogneiss (0.36 wt.…”
Section: Study Sitesmentioning
confidence: 99%
“…The Mg isotope determinations were thus performed at the end of the 19-year monitoring period and six years after the last application of dolomitic limestone at UDL. Soil water at UDL was collected by suction lysimeters from the depths of 30 and 50 cm [47]. At LYS and PLB, gravitational lysimeters installed at depths of 10 and 20 cm were complemented with suction lysimeters at the Isotope composition of atmospherically deposited elements in industrial areas can, in principle, differ along the catchment slope.…”
Section: Samplingmentioning
confidence: 99%
“…The more polluted site U Dvou Loucek (UDL) is located in the Eagle Mts., northern Czech Republic. The less polluted site Na Lizu (LIZ) is located in the Bohemian (Sumava) Forest Mts., southern Czech Republic (Figure , Table ). The areas of the UDL and LIZ catchments are 33 and 99 ha, respectively.…”
Section: Materials and Methodsmentioning
confidence: 99%
“…Both sites are equipped with a gauging station. A detailed δ 18 O-H 2 O study indicated a mean residence time of water within the UDL catchment of approximately 8 months.…”
Section: Materials and Methodsmentioning
confidence: 99%